Efetividade e sensibilidade com uso de géis clareadores experimental e comercial à base de peróxido de carbamida - Santana, Rosemary Soares de [UNESP] (2014)
This clinical study assessed tooth sensitivity (SD) and the effectiveness of home bleaching as well as the color relapse after the use of based on commercial carbamide peroxide gels (CP) containing potassium nitrate and fluoride (PF) and experimental gels (EX) also containing sodium tripolyphosphate (STP). A hundred patients, who underwent tooth whitening treatment, were divided randomly into 5 groups (n = 20/groups): 1) 10% carbamide peroxide experimental gel PF Mint (EX10); 2) 20% carbamide peroxide experimental gel PF Mint (EX20); 3) 10% commercial carbamide peroxide gel (Opalescence 10% Mint PF) (OP10); 4) 20% commercial carbamide peroxide (Opalescence 20% Mint PF) (OP20); 5) placebo 0% carbamide peroxide gel PF mint (PL). Bleaching was performed on a single arch of each patient for 2 hours during 14 days. In order to evaluate the color, it was used spectrophotometer, photographic analysis, and Vita 3D Master Bleachedguide in the periods: initial, 7 and 14 days after the start of the treatment and 30 days after the end to verify the color stability. The SD was daily evaluated, according in the following grades: absence, mild, moderate, substantial and severe. The results were analyzed by ANOVA (repeated measures) for measurement by spectrophotometer, Kruskal-Wallis and Dunn tests, 5% of significance to sensitivity to visual scale. Comparisons of shade guide the color analysis showed p < 0.05, and sensitivity to 0.0482 < 0.05. The whitening gel OP10 promoted better color results and minor sensitivity compared to the EX10. And the EX20 group showed greater lightening action with same level of sensitivity as the OP20 group. It was concluded that the groups OP10 and EX20 promoted the best results regarding the whitening with the smallest rate of sensibility when compared to the groups with the same concentrations and there was STP influence on the whithening effectiveness